Pre-plant application and different weed removal applications and their combinations caused positive effects on yield-related parameters - İdikut, Leyla and Uskutoğlu, Duygu and Çiftçi Sakin, Songül and Zulkadir, Gülay (Emirates Journal of Food and Agriculture, 2023)
In this study, the effect of corn on grain quality was investigated by applying different weed removal processes in corn plant. These, which was repeated for two years, four weed removal treatments [Hand hoe (H), hand and tractor hoe (HT), tractor hoe (T), and no-operation-control (C)] were tested on corn in a pre-treated [radish (R)] and an untreated [no front crop (NR)] field. According to the means of the applications for the years; thousand grain weight (TGW) and weight of ear grain (WEG) values were high in R, H and HT applications, while the lowest values were obtained in control applications. In protein content (PC), it has been noted that R application reduces the PC value while hoe applications gave parallel results with TGW and WEG. Rod ratio on the cob (RRC) and starch content (SC) values were positively affected by R and C applications. Finally, in the oil content (OC) value, it has been seen that the differences in the combination of the applications where the NR and C applications have insignificant but positive effects are more prominent. As a result, while R, H and HT applications and their combinations caused positive effects on yield-related parameters (TGW and WEG), some inconsistencies were observed in quality parameters (OC, SC and PC). It is thought that these discrepancies are caused by changes in the nutrient content of the soil and its acceptability by the plant, influenced by changes in the amount of precipitation. Keywords: agroecology; allelopathy; bio-herbicide; Raphanus sativus; Zea mays L.